Exploring evidence gaps in clinical trials in thermal burns care: an umbrella review - Sarah Dawson; Jane Blazeby; Alice Lee; Baljit Dheansa; Amber Young; Jelena Savović; Janine Evans; Riaz Qureshi; Robert Staruch; Jill Meirte; Suzannah Kinsella; Hollie Sarah Richards; et al. (BMJ Open)
Background Gaps in research evidence lead to research waste. In burns treatment, there is a paucity of reliable evidence or data. This contributes to inconsistent patient care, especially on a global scale, where low-resource countries often lack access to the latest research advancements. This umbrella review was undertaken as part of the James Lind Alliance Priorities in Global Burns Research Prioritisation Setting Partnership (PSP) and aimed to identify and assess the quality of evidence in thermal burns care. The objective was to map which interventions in thermal burns care are supported by a reliable evidence base and for which the evidence is lacking.Methods Systematic reviews of randomised controlled trials in thermal burns were identified and assessed using reliability criteria determined a priori. Multiple systematic review databases were searched in June 2023, including the Cochrane Library, KSR Evidence database and NIHR Journals Library. Summary of findings and, where available, Grading of Recommendations Assessment, Development and Evaluation was used to assess certainty of evidence. Reliable reviews were mapped onto clinical categories identified by patients, carers and healthcare professionals as part of the PSP.Results 232 systematic reviews were identified, of which 83 met reliability criteria and were included. The main reason for not meeting reliability criteria was poorly defined eligibility criteria (n=128). Of the 83 reliable reviews, most were conducted in pain (n=28) or wound management (n=14) and acute care (n=13). Certainty of evidence was mixed. Reviews mapped onto nine of the 17 clinical categories identified by the PSP.Conclusion This review summarises the available high-quality evidence in burns care and identifies evidence gaps, indicating that many important clinical questions remain unanswered. There is a discrepancy between the treatments investigated in high-quality research and the clinical areas considered as most important to stakeholders. These findings provide direction for future research to improve global burns care.